EFFECTS OF DIMINISHING FOREST AREA ON RAINFALL AMOUNT AND DISTRIBUTION IN NORTHEASTERN THAILAND - Tangtham, Nipon; Sutthipibul, Vasa (วารสารวนศาสตร์ไทย, 2022)
Based on 36 stations of 34 yr rainfall data (during 1951 to 1984) recorded by Royal Irrigation Department and the Meteorology Department together with the forest maps in different periods produced by Royal Forest Department and Faculty of Forestry, the effects of diminishing forest area in the Northeast on rainfall amount and distribution wihtin the region was investigated. Statistical analysis based on year-by-year observed data showed insignificant relationship between given periodical rainfall amount, i.e., monthly, seasonal and annual, and the remaining forest areas. When considering upon time-trend basis, statistical parameters obtained from using the moving average of time series 5, 10, 15, 20, 25, and 30 year indicated that rainfall amount tends to significantly decrease along with the depletion of forest area while the number of rainy day significantly increase.